The Lung Mucosa Environment in the Elderly Increases Host Susceptibility to Mycobacterium tuberculosis Infection. (29th March 2019) - Moliva, Juan I; Duncan, Michael A; Olmo-Fontánez, Angélica; Akhter, Anwari; Arnett, Eusondia; Scordo, Julia M; Ault, Russell; Sasindran, Smitha J; Azad, Abul K; Montoya, Maria J; Reinhold-Larsson, Nicole; Rajaram, Murugesan V S; et al.
Abstract: As we age, there is an increased risk for the development of tuberculosis (TB) caused by Mycobacterium tuberculosis ( Mtb ) infection. Few studies consider that age-associated changes in the alveolar lining fluid (ALF) may increase susceptibility by altering soluble mediators of innate immunity. We assessed the impact of adult or elderly human ALF during Mtb infection in vitro and in vivo. We identified amplification of pro-oxidative and proinflammatory pathways in elderly ALF and decreased binding capability of surfactant-associated surfactant protein A (SP-A) and surfactant protein D (SP-D) to Mtb . Human macrophages infected with elderly ALF–exposed Mtb had reduced control and fewer phagosome–lysosome fusion events, which was reversed when elderly ALF was replenished with functional SP-A/SP-D. In vivo, exposure to elderly ALF exacerbated Mtb infection in young mice. Our studies demonstrate how the pulmonary environment changes as we age and suggest that Mtb may benefit from declining host defenses in the lung mucosa of the elderly.